The prevalence and impact of Babesia canis and Theileria sp. in free-ranging grey wolf (Canis lupus) populations in Croatia - Ana Beck; Doroteja Huber; Adam Polkinghorne; Andrea Gudan Kurilj; Valerija Benko; Vladimir Mrljak; Slaven Reljić; Josip Kusak; Irena Reil; Relja Beck (Parasites & Vectors, 2017)
Abstract Background Babesia spp. and Theileria spp. are important emerging causes of disease in dogs. Alongside these domesticated hosts, there is increasing recognition that these piroplasms can also be found in a range of wild animals with isolated reports describing the presence of these pathogen in foxes (Vulpes vulpes) and captive grey wolves (Canis lupus). The prevalence and impact of these infections in free-ranging populations of canids are unknown. To gain a better insight into the epidemiology and pathogenesis of piroplasm infections in free-ranging grey wolves, pathological and molecular investigations into captive and free-ranging grey wolves in Croatia were performed. Results The carcasses of 107 free-ranging wolves and one captive wolf were the subjects of post-mortem investigations and sampling for molecular studies. A blood sample from one live captured wolf for telemetric tracking was also used for molecular analysis. PCR amplification targeting the 18S RNA gene revealed that 21 of 108 free-ranging wolves and one captive animal were positive for Theileria/Babesia DNA. Subsequent sequencing of a fragment of the 18S RNA gene revealed that 7/22 animals were positive for Babesia canis while the other amplified sequence were found to be identical with corresponding 18S rDNA sequences of Theileria capreoli isolated from wild deer (15/22). Haematological and cytological analysis revealed the presence of signet-ring shaped or pear-shaped piroplasms in several animals with the overall parasite burden in all positive animals assessed to be very low. Pathological investigation of the captive animal revealed fatal septicemia as a likely outcome of hemolytic anaemia. There was little or no evidence of hemolytic disease consistent with babesiosis in other animals. Conclusion Importantly, the presence of B. canis in free-ranging grey wolves has not been described before but has been reported in a single fox and domestic dogs only. That B. canis infections cause disease in dogs but have little impact on wolf health possibly suggests that the wolf is the natural and the domestic dog is a secondary host. Surprisingly, the frequent finding of Theileria capreoli in wolves suggests that this Theileria species is not restricted to ungulates (cervids) but commonly infects also this carnivore species. Nevertheless, the potential role that these asymptomatically infected animals may play in the dispersal of these pathogens to susceptible sympatric species such as domesticated dogs requires further investigation.